The Frequency of Human Papillomavirus Positivity in Iranian Patients with Head and Neck Squamous Cell Carcinoma - Mitra Rezaei; Mahboobeh Karimi-Galougahi; Azin Kheradmand; Mihan Pourabdollah Toutkaboni; Hassan Mir Mohammad Sadeghi; Alireza Abdollahi; Amirnader Emami Razavi; Ali Safavi Naini; Farahnaz Bidari- Zerehpoosh (Iranian Society of Pathology, 2021)
Background & Objective: Human papillomavirus (HPV) has been associated with prognosis in patients with head and neck squamous cell carcinoma (HNSCC). Similar to the global studies, different prevalence rates of this viral infection have been reported in Iran. Therefore, we aimed to report the prevalence of this virus and its significance in HNSCC patients.Methods: Patients who were referred to the five hospitals of Tehran city from May 2018 to May 2019 were enrolled in this study. All patients were diagnosed with HNSCC based on pathologic study. The pathologic disease staging was defined, and DNAs were extracted from the fresh tissue samples via kits. After polymerase chain reaction (PCR), HPV positive samples were evaluated for determining genotypes and data analysis.Results: Of the 46 patients, three patients (6.5%) had positive HPV with the following subtypes: 18 (in two patients), 52 (in three patients), 61 (in two patients), 67, and 73.Comparison of variables between the groups with and without HPV showed a significant difference based on the tumor's lymphatic invasion (p =0.041), peripheral lymph node involvement (p =0.008), and histologic grade (p =0.011), but there was no statistically significant difference in terms of other variables such as age, primary tumor site, size, pathologic stage, vascular or perineural invasion, metastasis, smoking, and alcohol consumption.Conclusion: HPV positivity is an important factor in the lymphatic invasion, peripheral lymph node involvement, and histologic grade of cases with HNSCC and should be further investigated for its effect on prognosis.